48 Findings from a scoping exercise of adult acute hospital trusts in england recording decisions about treatment escalation for those at risk of deterioration at the end of life. Issue 3 (1st September 2017) - Lund, Susi; Cummings, Amanda; May, Carl; Richardson, Alison; Campling, Natasha; Myall, Michelle
Abstract : Introduction: Planning and communicating treatment decisions in a context of clinical uncertainty presents a key challenge. Increasing evidence supports the desirability of documenting a care-plan that addresses options about treatment escalation (Treatment Escalation Plan (TEP)) ensuring quality of healthcare for patients, in line with their wishes, prevention from distressing treatments and unnecessary harm as end of life approaches (Dalgaard et al., 2010, Carey et al., 2015, Obolensky et al., 2010, Gott et al., 2011, National Confidential Enquiry into Patient Outcome and Death, 2012, Fritz et al., 2013). Aims: To ascertain current procedures for recording treatment decisions in situations of clinical uncertainty. To identify and characterise key components of TEPs and understand the implications of these when incorporated into clinical practice. Method: A scoping exercise of all UK NHS adult acute Trusts. Telephone interviews were conducted to gain more indepth knowledge of processes and analysed using directed content analysis. Where a TEP was in use, content analysis was conducted to understand the structure and information required to complete them. Results: 55/150 Trusts provided details of systems used. Of these 43 had experience of using a TEP, 29 of which had been formally evaluated. A further 6 were sourced through online searches. There was wide variation in the processes used. Forms consistently attended to seven key components: Resuscitation; Communication; ceilings of care; supportive care; capacity; transferability; colour/format. Conclusion: TEPs are valuable in ensuring patients' dignity and comfort when faced with acute pathophysiological deterioration at end of life and have potential to minimise harm from unnecessary and/or unwanted investigations and treatment. However, inconsistency in availability and incorporation into practice has implications for quality and consistency of patient care. References: . CAREY, I., SHOULS, S., BRISTOWE, K., MORRIS, M., BRIANT, L., ROBINSON, C., CAULKIN, R., GRIFFITHS, M., CLARK, K., KOFFMAN, J. & HOPPER, A. 2015. Improving care for patients whose recovery is uncertain. The AMBER care bundle: design and implementation. BMJ Supportive & Palliative Care, 5, 405–411. . DALGAARD, K. M., THORSELL, G. & DELMAR, C. 2010. Identifying transitions in terminal illness trajectories: a critical factor in hospital-based palliative care. International Journal Of Palliative Nursing, 16, 87–92. . FRITZ, Z., MALYON, A., FRANKAU, J. M., PARKER, R. A., COHN, S., LAROCHE, C. M., PALMER, C. R. & FULD, J. P. 2013. The Universal Form of Treatment Options (UFTO) as an alternative to Do Not Attempt Cardiopulmonary Resuscitation (DNACPR) orders: a mixed methods evaluation of the effects on clinical practice and patient care. Plos One, 8, e70977–e70977. . GOTT, M., INGLETON, C., BENNETT, M. I. & GARDINER, C. 2011. Transitions to palliative care in acute hospitals in England: qualitative study. BMJ Supportive & Palliative Care, 1, 42–48. . NATIONAL CONFIDENTIAL ENQUIRY INTO PATIENT OUTCOME AND DEATH2012. Time to interevene? : NCEPOD. . OBOLENSKY, L., CLARK, T., MATTHEW, G. & MERCER, M. 2010. A patient and relative centred evaluation of treatment escalation plans: a replacement for the do-not-resuscitate process. J Med Ethics, 36, 518–20.